HUBUNGAN KUALITAS PELAYANANROOM BOY DENGAN KEPUASAN TAMU MENGINAP DI HOTEL AXANA PADANG - Berutu, Feronika; Yuliana, Yuliana; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2015)
The purpose of this research is to knowthe correlation between service quality of room boy with stisfaction of guest stay at Hotel Axana Padang.The population amount are 1.711. people who are stay at Hotel Axana Padang, sample selection techniques in the study is using incidental-non probability sampling. The amount of sample are 95people. Data collection techniques is using a structured questionnaire based on Likert scale that has been tested for validity and reliability. Based on the survey find, the relationshipBetween Service Ouality of Room Boy with Satisfaction of guest shows positive with the value of correlation (r) 0,634 and significant 0,000. Key words: service ouality of room boy, satisfaction of guest